Fundamentals of nursing : human health and function - Craven, Ruth F.; Hirnle, Constance J.; Jensen, Sharon, 1955- (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2013)
"As the healthcare system grows more complex, so does the pool of nursing candidates. You and your fellow students come with different skill sets and represent a wide range of backgrounds. To keep up, nursing schools are expanding the variety of courses in their curricula and adding new teaching methods and media to accommodate different learning styles. Still, all nursing students have one thing in common: They need a framework--a system for acquiring knowledge and putting it to work. The right framework simplifi es the whole process of clinical thinking. It helps you prioritize information so that you don't feel overwhelmed. It lets you work in a logical sequence and process data calmly and effi ciently. It teaches you to think about each case in a meaningful, systematic way. It builds intuition, so you can instantly grasp the kinds of problems you're up against. Most important, working within a proven framework helps you protect your patients' safety and ensure the best possible outcomes for those under your care. That's why the system we've devised for this book is so important"--
Includes bibliographical references and index.
Keywords: Nursing; Nursing Care; Nursing Process; Nursing